A STUDY ON RELATIONSHIP BETWEEN CAMPUS FACILITIES AND STUDENT’S SATISFACTION IN UITM KELANTAN - Siti Nur Zahirah Omar,; Shafiqah Hanim Ramli,; Nor Mazilah Mahtar,; Nur Farah Nabila Sariman,; Nur Amylia Natasha Abd Fatah,; Tengku Nur Eleana Tengku Rujhan, (Journal of Islamic, Social, Economics and Development, 2024)
The main purpose of this research is to study the relationship between campus facilities and student satisfaction in UiTM Kelantan. This study aims to investigate the relationship between classroom facilities, library facilities, environmental safety, accommodation facilities, sports facilities, and student satisfaction. The research method used a survey-based questionnaire with 364 respondents to evaluate the relationship between campus facilities and student satisfaction. The quantitative research method used a survey-based questionnaire to evaluate the relationship between campus facilities and student satisfaction. A total of 364 students from UiTM Kelantan consisting of UiTM Kota Bharu and Machang responded to the distributed questionnaire. Analysis of the quantitative data revealed that classroom facilities, library facilities, environmental safety, accommodation facilities, and sports facilities have positive significant relationships with student satisfaction.